Svoboda: Wagner Joseph Svoboda's Scenography for Richard Wagner's Operas (Wesleyan University Press, 1983)
In Svoboda: Wagner, Jarka Burian (1927-2005) presents an in-depth exploration of the collaboration between one of Germany's greatest composers and the Czech Republic's most innovative multimedia scene designer. More familiar with Svoboda's (1920-2002) work, Burian translates the artistic collaboration between Svoboda and Wagner through the production of The Ring of the Nibelung, one of opera's most complicated pieces. Examining stage orchestration, acting methods, and architecture, Burian attempts a view into modern scenography and the inner workings of the theatre for the public reader.